Concepts and challenges in the use of mesenchymal stem cells as a treatment for cartilage damage in the horse. (June 2018) - Zayed, Mohammed; Adair, Steve; Ursini, Tena; Schumacher, James; Misk, Nabil; Dhar, Madhu
Abstract: Osteoarthritis (OA), the most common form of joint disease affecting humans and horses, is characterized by the advance and decline of cartilage and loss of function of the affected joint. The progression of OA is steadily accompanied with biochemical events, which interfere with the cytokines and proteolytic enzymes responsible for progress of the disease. Recently, regenerative therapies have been used with an assumption that mesenchymal stem cells (MSCs) possess the potential to prevent the advancement of cartilage damage and potentially regenerate the injured tissue with an ultimate goal of preventing OA. We believe that despite various challenges, the use of allogenic versus autologous MSCs in cartilage regeneration, is a major issue which can directly or indirectly affect the other factors including, the timing of implantation, dose or cell numbers for implantation, and the source of MSCs. Current knowledge reporting some of these challenges that the clinicians might face in the treatment of cartilage damage in horses are presented. In this regard we conducted two independent studies. In the first study we compared donor matched bone marrow and synovial fluid – derived equine MSCs in vitro, and showed that the SFMSCs were similar to the BMMSCs in their proliferation, expression of CD29, CD44 and CD90, but, exhibited a significantly different chondrogenesis. Additionally, 3.2–21% of all SFMSCs were positive for MHC II, whereas, BMMSCs were negative. In the second study we observed that injection of both the autologous and allogenic SFMSCs into the tarsocrural joint resulted in elevated levels of total protein and total nucleated cell counts. Further experiments to evaluate the in vivo acute or chronic response to allogenic or autologous MSCs are imperative. Highlights: Structure of the articular cartilage, and current therapies are described. Regenerative medicine approaches offer promising novel means for osteoarthritis repair in clinical application. The review referred to in vitro studies of stem cells and concludes by considering challenges of their clinical uses.